Peningkatan Hasil Pembelajaran Lompat Jauh Melalui Pendekatan Bermain Longu pada Siswa Kelas IV SDN 37 Ampenan - Kurnia Zainuri (Jurnal Paedagogy, 2020)
The purpose of this study is to improve the learning outcomes of long jump through longu playing approach to grade IV students of SDN 37 Ampenan. This study uses a class action research method using 2 cycles with the subject of the research being grade IV students, amounting to 21 students. The research instruments used in this study were observation and questionnaires. Analysis of the data of this study uses quantitative and qualitative descriptive. The results of this study indicate that through the approach of playing kangaroo jump on the material of long jump by using aqua bottle media and pralon as a learning facility and infrastructure can improve student learning outcomes in grade IV 37 Public Elementary School Ampenan. Suggestions based on the results of this study are expected for elementary school physical education teachers to use Classroom Action Research (CAR) in learning, teachers can vary the various forms of games in learning, and aqua bottle and pralon can be used to overcome the shortage of teaching aids in learning long jump.